Mapping the Landscape of Rubric-Based Assessment Studies: A Bibliometric Review - Loso Judijanto (The Eastasouth Journal of Learning and Educations, 2026)
This study aims to map the intellectual structure and research trends of rubric-based assessment through a comprehensive bibliometric analysis. Using data retrieved from the Scopus database, this study examines publications from 2000 to 2025 to identify the evolution, key contributors, and thematic development of research in this field. Bibliometric techniques were employed using VOSviewer to analyze co-authorship networks, keyword co-occurrence, and thematic clustering. The results reveal that rubric-based assessment research has developed into three major domains: pedagogical application, applied professional education, and psychometric validation. Early studies focused on establishing validity, reliability, and measurement rigor, while subsequent research emphasized instructional integration, formative assessment, and competency-based learning. More recent trends indicate a growing interest in the integration of artificial intelligence, large language models, and digital learning systems in rubric-based assessment practices. The findings also show that while traditional themes such as teaching and educational measurement remain dominant, emerging technology-driven approaches are shaping future research directions. This study contributes to the literature by providing a systematic overview of the knowledge structure and evolution of rubric-based assessment research, offering insights for researchers and educators in developing more effective, adaptive, and technology-enhanced assessment frameworks.